2021
DOI: 10.3389/fonc.2021.675873
|View full text |Cite
|
Sign up to set email alerts
|

Prior Therapy With Pegylated-Interferon Alfa-2b Improves the Efficacy of Adjuvant Pembrolizumab in Resectable Advanced Melanoma

Abstract: Combination immunotherapy can overcome the limited objective response rates of PD-1 blockade. Interferon alpha (IFN-α) has been proven to be effective in modulating immune responses and may enhance the clinical responses to PD-1 blockade. According to clinical practice guidelines, IFN-α was recommended as adjuvant therapy for stage IIB/C melanoma patients. However, the impact of prior IFN-α therapy on the efficacy of subsequent PD-1 blockade in melanoma has not been previously reported. Therefore, we performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…In addition, a retrospective analysis of Jia et al . 65 demonstrated that front-line therapy with IFN may enhance the efficacy of later-line adjuvant therapy with pembrolizumab, which offered the possibility of sequential treatment modalities of IFN and pembrolizumab in resected melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a retrospective analysis of Jia et al . 65 demonstrated that front-line therapy with IFN may enhance the efficacy of later-line adjuvant therapy with pembrolizumab, which offered the possibility of sequential treatment modalities of IFN and pembrolizumab in resected melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…64 This combination therapy was also well tolerated, but since Keynote-020 is a single-arm trial, these findings should be interpreted with caution. In addition, a retrospective analysis of Jia et al 65 demonstrated that front-line therapy with IFN may enhance the efficacy of later-line adjuvant therapy with pembrolizumab, which offered the possibility of sequential treatment modalities of IFN and pembrolizumab in resected melanoma.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…While IFN-α has been shown to potentially improve recurrence-free survival (RFS) and overall survival (OS) in patients with high-risk melanoma, its effects on OS remain questionable according to some oncologists [28]. Furthermore, adjuvant therapy with PD-1 or BRAF/MEK inhibitors has shown superior results and is being tested in combination with other options such as immunotherapy, further questioning the efficacy of IFN-α as a standalone treatment [29,30]. Despite extensive research, the exact mechanism of IFN-α action in MM remains unclear [3].…”
Section: Discussionmentioning
confidence: 99%
“…Kaliki Ein nachrangiger Ansatz der systemischen Therapie, der hier dennoch zu erwähnen ist, ist der Einsatz von Interferonen. Beispielsweise verbessert eine Vortherapie mit pegyliertem Interferon Alpha-2b das Ansprechen von fortgeschrittenen resektablen Melanomen auf adjuvante Pembrolizumab-Therapie [43]. Außerdem kann Interferon Alpha-2a In Kombination mit 13-cis-Retinsäure der systemischen Therapie von fortgeschrittenen Plattenepithelkarzinomen dienen [44].…”
Section: Konventionelle Chemotherapieunclassified